2012
DOI: 10.1111/j.1365-2265.2011.04198.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and gender‐specific prevalence of carotid atherosclerosis and its association with metabolic syndrome in Hangzhou, China

Abstract: These results indicate that CA and CP have become a major public health problem in China. MetS and its components were associated with an increased prevalence of CA and CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
9
21
0
Order By: Relevance
“…In other words, MetS predicted the occurrence of new carotid plaque and may be correlated with changes in IMT over time. These results are consistent with the findings of several longitudinal 15,16,23,24) and cross-sectional studies 14,25,26) that addressed the relationships between MetS, carotid plaque and C-IMT. In the present study, the presence of carotid plaque was associated with accelerated C-IMT changes (Cont Table 1 stress and proinflammatory signaling in the vessel wall 38) .…”
Section: Discussionsupporting
confidence: 81%
“…In other words, MetS predicted the occurrence of new carotid plaque and may be correlated with changes in IMT over time. These results are consistent with the findings of several longitudinal 15,16,23,24) and cross-sectional studies 14,25,26) that addressed the relationships between MetS, carotid plaque and C-IMT. In the present study, the presence of carotid plaque was associated with accelerated C-IMT changes (Cont Table 1 stress and proinflammatory signaling in the vessel wall 38) .…”
Section: Discussionsupporting
confidence: 81%
“…Men were likely to have extracranial atherosclerosis, which has been proved in other population. 26 These results are similar to those of Flora et al, 10 who found that the frequency of cerebral atherosclerosis increases more rapidly in women after the sixth decade. In our study, elderly women have more diabetes mellitus, hypertension, hyperlipidemia, and history of heart disease, which can help explain the difference.…”
Section: Sex Difference In Icassupporting
confidence: 82%
“…To compare our results with previous studies, we searched PubMed to identify population‐based studies that reported the prevalence of CA detected by ultrasound in China, and summarized findings are shown in Table 4. Of these previous studies,16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 only the CKB (China Kadoorie Biobank) study included a large sample of participants (N=24 822) from multiple geographic regions in China16; all other studies were geographically local. The CKB study reported that the overall prevalence of carotid plaque was 31%, which was much higher than the prevalence of 13.9% in the present study; however, the CKB study included participants with stroke (5.4%) or coronary heart disease (7.5%).…”
Section: Discussionmentioning
confidence: 99%